2014
DOI: 10.1111/bij.12306
|View full text |Cite
|
Sign up to set email alerts
|

Lower body mass and higher metabolic rate enhance winter survival in root voles,Microtus oeconomus

Abstract: Although the biological significance of individual variation in physiological traits is widely recognized, studies of their association with fitness in wild populations are surprisingly scarce. We investigated the effect of individual phenotypic variation in body mass, resting (RMR) and peak metabolic rates (PMR) on mortality of the root vole Microtus oeconomus. Body mass and metabolic rates varied significantly among consecutive years and were also age dependent, as individuals born in late summer and autumn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 55 publications
6
36
0
Order By: Relevance
“…Under natural conditions the root voles feed almost exclusively on sedges (Tast, 1966), and therefore they probably suffer from even more intense mucosal shedding than that reported here. In our recent study, we found that high densities of the root vole population inhabiting homogenous sedge wetland induces an increase of the silicon concentration in sedges at the end of summer , which, in turn, is followed by an increased mortality of larger (heavier) individual voles during early winter Zub et al, 2014). Thus, our laboratory experiment provides a mechanistic explanation to the field observations by showing that a sedge-dominated diet can reduce the intestinal absorptive surface.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Under natural conditions the root voles feed almost exclusively on sedges (Tast, 1966), and therefore they probably suffer from even more intense mucosal shedding than that reported here. In our recent study, we found that high densities of the root vole population inhabiting homogenous sedge wetland induces an increase of the silicon concentration in sedges at the end of summer , which, in turn, is followed by an increased mortality of larger (heavier) individual voles during early winter Zub et al, 2014). Thus, our laboratory experiment provides a mechanistic explanation to the field observations by showing that a sedge-dominated diet can reduce the intestinal absorptive surface.…”
Section: Discussionsupporting
confidence: 63%
“…Our previous studies showed that changes in the silicon concentration in fibrous tussock sedge (Carex appropinquata Schumacher 1801) were induced by a high density of cyclical population of the root voles (Microtus oeconomus Pallas 1776) at the end of the previous summer. We also found that smaller (lighter) voles were characterised by lower mortality during early winter Zub et al, 2014), which might be correlated with the low quality of their food base. However, the underlying proximate mechanism promoting smaller individuals is not known.…”
Section: Introductionsupporting
confidence: 50%
“…If positive associations between N/L ratio, body mass and survival hold, they indicate that the high N/L ratio manifests in the ability to combat already developing infection, rather than its contraction. This is in agreement with the analyses of Zub et al [10], which show that survival was not significantly affected by age of individual root voles in either early or late winter.…”
Section: Discussionsupporting
confidence: 93%
“…Our results concur with Zub et al's study [10] in demonstrating that cPMR in voles is positively associated with winter survival (figure 2a), most likely through enhancing swim-elicited aerobic performance in a frequently flooded habitat. Our findings from early winter also agree with Downs et al [5], who demonstrated an inverse association between induced (not constitutive) innate immunity and cPMR (elicited by forced exercise) in laboratory mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation